A coalgebraic approach to fuzzy automata - Guilherme, Ricardo Jorge Pratas (2016)
In this thesis, we make a coalgebraic description of fuzzy automata allowing their integration in much general context. Thus, results obtained indivudually to fuzzy automata end up to be consequence of their coalgebraic description. In particular, a coalgebraic definition of the fuzzy language recognized by a fuzzy automaton is obtained. And, by defining a monad for fuzzy sets, a functor that describes a determinization process via a generalization of the powerset construction is obtained.